Adverse event registry analysis of an EMS system in a low resource setting: a descriptive study - Geraty, Sian (Division of Emergency Medicine, 2019)
Introduction Out of hospital emergency medical service patients present unique challenges and ample opportunities for medical error to occur. Identifying medical error is important for mitigating future risk and improving patient safety. Hypothesis/problem Our study describes the adverse event registry of an emergency medical service system in a low resource setting over a six-year period. Methods The Western Cape Emergency Medical Services Adverse Event Registry were reviewed for the period 1 January 2010 to 31 December 2015. From these, all cases classified as an adverse event or near miss were extracted for in depth review. Demographics, type of error, and types of recommendations implemented are reported. Results Altogether 106 (69%) adverse events and 47 (31%) near misses were reported over the six-year period. The mean age of patients was 31 years (standard deviation ±24.8). Of these 65 (42%) cases were adult medical patients, 31 (20%) adult trauma patients, 15 (10%) obstetric patients and 42 (27%) paediatric patients. The caseload was observed to increase over the six-year period, whilst system medical errors decreased and individual medical errors increased over the same period. Conclusion In this low resource emergency medical service system, individual medical errors increased and system medical errors decreased as more recommendations derived from adverse events caused by the system errors were implemented. This created a greater need for individual and group training of EMS clinical providers. We recommend further research in order to adequate describe the reason for the increase individual medical error, as well as to find more effective means of detecting adverse events and near misses in this population.